Visually Estimated RESOLVE Score Based on Coronary Computed Tomography to Predict Side Branch Occlusion in Percutaneous Bifurcation Intervention. Issue 3 (May 2021) - Michalowska, Anna M.; Grodecki, Kajetan; Staruch, Adam D.; Kepka, Cezary; Wolny, Rafal; Pregowski, Jerzy; Kruk, Mariusz; Debski, Mariusz; Debski, Artur; Michalowska, Ilona; Witkowski, Adam; Opolski, Maksymilian P.
Abstract : Purpose: The quantitative RESOLVE (Risk prEdiction of Side branch OccLusion in coronary bifurcation interVEntion) score derived from coronary computed tomography angiography (coronary CTA) was developed as a noninvasive and accurate prediction tool for side branch (SB) occlusion in coronary bifurcation intervention. We aimed to determine the ability of a visually estimated CTA-derived RESOLVE score (V-RESOLVE score) to predict SB occlusion in coronary bifurcation intervention. Materials and Methods: The present study included 363 patients with 400 bifurcation lesions. CTA-derived V-RESOLVE score was derived and compared with the quantitative CTA-derived RESOLVE score. The scoring systems were divided into quartiles, and classified as the high-risk and non–high-risk groups. SB occlusion was defined as any decrease in thrombolysis in myocardial infarction flow grade after main vessel stenting. Results: In total, 28 SB occlusions (7%) occurred. The concordance between visual and quantitative CTA analysis showed poor to excellent agreement (weighted κ range: 0.099 to 0.867). The area under the receiver operating curve for the prediction of SB occlusion was significantly higher for the CTA-derived V-RESOLVE score than for quantitative CTA-derived RESOLVE score (0.792 vs. 0.709, P =0.049). The total net reclassification index was 42.7% ( P =0.006), and CTA-derived V-RESOLVE score showed similar capability to discriminate between high-risk group (18.6% vs. 13.8%, P =0.384) and non–high-risk group (3.8% vs. 4.9%, P =0.510) as compared with quantitative CTA-derived RESOLVE score. Conclusions: Visually estimated CTA-derived V-RESOLVE score is an accurate and easy-to-use prediction tool for the stratification of SB occlusion in coronary bifurcation intervention. Abstract : Supplemental Digital Content is available in the text.